EVALUATION OF POPULATIONS OF PEST INSECTS IN THE ASSOCIATION SUGAR CANE - BEAN AND ITS RELATION TO PERFORMANCE - GARCÍA, JORGE; CARDONA, CÉSAR; RAIGOSA, JUÁN (Revista Colombiana de Entomología, 1979)
The present study on beans (Diacol-Calima) in association with sugar cane (CP 57603) had the main objectives of determining optimum planting time of beans with respect to sugar cane, the agronomic feasibility of such association and measure its influence on their respective insect pest populations and on yields. Nymphal and adult populations of Empoasca Kraemeri Ross & Moore, as well as of crysomelids, Cerotoma facialis (Erickson) and Diabrotica balteata Le Conte were always lower in associated than in monocropped beans, this effect was significantly marked when beans were planted 45 days after sugar cane. The incidence of insect pests in sugar Gane was very low, so no significant differences were detected between treatments. In early associations competence by beans was not reflected on sugar cane yields; the best treatments, with good crop development, least competence due to intercropping and highest yields were those in which beans were planted 15 days after sugarcane seeding simultaneously with it. No insecticide applications were necessary. The results suggest that intercropping of beans and sugar cane is agronomically and entomologically feasible under the Cauca Valley (Colombia) conditions.